Identidad cultural de los pobladores y desarrollo del turismo en la comunidad Shipibo Konibo Contamana 2021 - Pacho Pizango, David (2022)
The objective of the research was to determine the relationship between cultural identity and the development of tourism in the Shipibo Konibo Contamana 2021 community. Applied type study, descriptive - correlational level with non-experimental design, for this, it has been taken as a study sample a 349 inhabitants of said community, for data collection the survey technique and the questionnaire instrument were chosen. Therefore, the research concludes that the cultural identity in the Shipibo Konibo Contamana community is regular, due to the fact that there are people who do not feel identified with their culture in other places, it is not difficult for them to adapt to other traditions foreign to them. their community, quickly adopting other customs, among other factors that demonstrate the community's lack of identity. Likewise, it was determined that the development of tourism is regular, due to the lack of investment in tourism infrastructure, low employment promotion, little promotion of intercultural relations, disinterest of the authorities in the care and protection of tourists, minimal is the concern of local authorities in the improvement of access routes, restoration and maintenance of tourist resources. In general, it has been possible to determine that there is a relationship between cultural identity and the development of tourism in the Shipibo Konibo Contamana community in 2021, with a bilateral significance of 0.000 and a correlation of 0.845, which is very strong positive.